ANALISIS KOMPARASI RELEVANSI NILAI INFORMASI AKUNTANSI SEBELUM DAN SESUDAH ADOPSI PENUH IFRS DI INDONESIA - Sugi Suhartono (Universitas Bunda Mulia, 2018)
Many companies had adopted but there is a differences on the quality of the accounting report that were created before and after the adoption that has not been studied by academics, because of this researcher wants to investigate whether there are any differences in value relevance of accounting information before and after the full adoption of IFRS. Based on regulation theory, signalling theory, market efficient theory and clean surplus theory. The gap between action that were taken by management and the will of shareholders could possibly happen when the asymmetric information disrupt the capability of investor to supervise managerial level and lead the investor to make a wrong decision. Samples of this study consisted of 16 companies that are part of LQ 45 Index of Indonesia Stock Exchange. Purposive Sampling method is used to take the sample. The data analysis technique used to test the hypothesis is Chow Test. Chow test shows F value (0.57985) is smaller than F table (2.71). Then, in testing of the coefficient of determination, which the value of adjusted R2 before the full adoption of IFRS is 85.7% and after the full adoption of IFRS is 82.2%. This shows a 3.5% reduction of adjusted R2. The reduction of the adjusted R2 indicates that the adjusted R2 can not be explained by measuring stock prices, earnings per share, and book value per share after full adoption of IFRS. Based on the study results show that the full adoption of IFRS does not affect the relevance of the value of accounting information on companies listed in the LQ 45 index. Keyword : Value Relevance, Profit, Equity Book Value, IFRS Adoption